2017
DOI: 10.1016/j.medici.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold design for artificial tissue with bone marrow stem cells

Abstract: The obtained results suggest that electrospinning technology and femtosecond laser micro-structuring could be employed for the development of multi-layer scaffolds. Different biopolymers, such as PLA, fibrin, and collagen, could be used as appropriate environments for cell inhabitation and as an inner layer of the multi-layer scaffold. PI could be suitable as a barrier blocking cell migration from the scaffold. However, additional studies are needed to determine optimal parameters of inner and outer scaffold l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…They can provide irregular and rough surface, which is conducive to cell adhesion and proliferation, and is sought after. 54 , 73 …”
Section: Drugs Delivered In Bone Tissue Engineering Composite Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can provide irregular and rough surface, which is conducive to cell adhesion and proliferation, and is sought after. 54 , 73 …”
Section: Drugs Delivered In Bone Tissue Engineering Composite Scaffoldsmentioning
confidence: 99%
“…They can provide irregular and rough surface, which is conducive to cell adhesion and proliferation, and is sought after. 54,73 MicroRNAs (miRNA) are a kind of noncoding single-stranded RNA molecules with a length of about 22 nucleotides encoded by endogenous genes, which are involved in the regulation of post-transcriptional gene expression in bone tissues. In recent years, the use of microRNAs to induce osteogenesis and promote neovascularization of osteoblasts is expected to become an alternative approach for bone tissue engineering.…”
Section: Stem Cells and Micrornamentioning
confidence: 99%
“…Various studies have successfully applied 3D printed scaffolds in promoting chondrogenesis of bone mesenchymal stem cells (BMSCs) [2,3]. Further studies improved the precise and accurate 3D structures for cartilage tissue engineering [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 3D printed PLA scaffolds can enrich BCSC niche in a MDA-MB-231 cell line in less time than other types of scaffolds can. Noreikaité et al demonstrated that PLA electrospun scaffolds ensured a suitable environment for cell growth with mesenchymal stem cells which were capable of spreading after three days of cultivation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%